EXAMINING THE ROLE OF COMPUTERS IN THE TEACHING AND LEARNING OF GEOGRAPHY AT ADVANCED LEVEL: A FOCUS ON SIX HIGH SCHOOLS IN WARREN PARK/ MABELREIGN DISTRICT, ZIMBABWE - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2016)
The advent of modern technology has been a welcome development in education. It is a development that was envisaged to make teaching and learning easier, enjoyable and accessible to all who require it. E-learning has now been used to support the traditional methods of teaching and learning. The introduction of computers in education has witnessed a change from the traditional approaches to teaching to the use of computer assisted instruction (CAI). To support the use of modern technology, the Zimbabwean government has distributed computers to both primary and secondary schools. To complement government effort, parents and other stakeholders through School Development Committees, School Development Associations and Old Students Associations have contributed to the acquisition of educational resources that include computers. All these efforts were meant to facilitate teaching and learning in schools. Despite these efforts the performance in Geography at Advanced level has remained low compared to other subjects. The purpose of the study was to examine the extent to which computer assisted instruction (CAI) has been utilised in the teaching of Geography at Advanced level. The study also made an analysis of other approaches used in the teaching and learning of Geography. The study used the mixed methodology and the descriptive survey design. Data was collected using structured questionnaires, open-ended questionnaires, and face-to-face interviews. The six schools were conveniently sampled and the respondents were randomly selected. The study concluded that there are many factors that have contributed to poor performance in Geography at A level. Some of the factors that emerged were lack computer skills for both teachers and pupils. There was limited use of computers in map work. Other areas that did not receive serious consideration in the teaching and learning of Geography were field work and hands- on approach to teaching and learning Geography as a subject. The study recommends that there be a paradigm shift in terms of the methods used in the teaching and learning of Geography at Advanced level.